HISTORICAL NECESSITY OF THE SECOND VATICAN COUNCIL - Thonippara, Francis (Asian Horizons, 2012)
The historical background for the convocation of the three modern councils, i.e. Council of Trent, First Vatican Council and the Second Vatican Council, is different. Council of Trent was the Catholic response to the Protestant Reformation and a delayed attempt of the Catholic Church to reform the Church, which was urgently felt in the Church, and its impact is experienced even today. After many postponements, Pope Paul III had the moral courage to convoke the Council of Trent to reform the Church. Inner renewal of the Church, definition of dogmas and the pastoral care of the souls were the main aims of the Council. Pope Pius IX was not mentally prepared to assimilate and appreciate the modern concepts like democracy, unified Italy, collegial character of the Church, etc. After defining the dogma of Immaculate Conception, publishing the Syllabus of Errors and having feared the attack on papal infallibility, the Pope decided to convene a Council and define the infallibility of the Pope. However, due to the Franco-Prussian war, the Council was abruptly brought to an end and it did not have a natural conclusion. After the declaration of Rome as the capital of the unified Italy, Pope Pius IX was practically a prisoner in Vatican.